The impact of taphonomic data on phylogenetic resolution: Helenodora inopinata (Carboniferous, Mazon Creek Lagerstätte) and the onychophoran stem lineage. Issue 1 (December 2016) - Murdock, Duncan; Gabbott, Sarah; Purnell, Mark
Abstract Background The origin of the body plan of modern velvet worms (Onychophora) lies in the extinct lobopodians of the Palaeozoic.Helenodora inopinata, from the Mazon Creek Lagerstätte of Illinois (Francis Creek Shale, Carbondale Formation, Middle Pennsylvanian), has been proposed as an intermediate between the "weird wonders" of the Cambrian seas and modern terrestrial predatory onychophorans. The type material ofH. inopinata, however, leaves much of the crucial anatomy unknown. Results Here we present a redescription of this taxon based on more complete material, including new details of the head and posterior portion of the trunk, informed by the results of experimental decay of extant onychophorans.H. inopinata is indeed best resolved as a stem-onychophoran, but lacks several key features of modern velvet worms including, crucially, those that would suggest a terrestrial mode of life. Conclusions The presence ofH. inopinata in the Carboniferous demonstrates the survival of a Cambrian marine morphotype, and a likely post-Carboniferous origin of crown-Onychophora. Our analysis also demonstrates that taphonomically informed tests of character interpretations have the potential to improve phylogenetic resolution.